Advanced practice in endocrinology nursing. (Switzerland : Springer, 2019)
This book provides a comprehensive guide for nurses practicing in any area of endocrinology and at any level of expertise. Endocrinology Nursing is a fast-developing specialty with nurses performing advanced roles and expanding their practice to run independent nurse-led services. Supported by the European Society of Endocrinology (ESE) and edited by members of the ESE Nurses Working Group, this is the first book ever published specifically for endocrine nurses. It is also an excellent resource for endocrinology specialty trainees, general practitioners, medical and nursing students, expert patients and nurses working in specialties such as fertility, osteoporosis, oncology, obesity, urology and gynaecology, who look after patients with endocrine-related disorders. This volume includes 13 sections and 69 chapters providing a comprehensive overview of adult and paediatric endocrinology but also a section on advanced practice, role development and nursing research. It has been written by an international team of more than 100 eminent nurses, physicians, surgeons, psychologists and other healthcare professionals, which makes this book a valuable resource for any multidisciplinary team. Many patient advocacy groups have contributed with case studies which emphasises the close working relationships with patients.
La función de los autores fue determinada por el catalogador
También disponible en formato EPUB